Profibrotic cytokines in aqueous humour correlate with aqueous flare in patients with rhegmatogenous retinal detachment. Issue 4 (26th January 2013) - Hoerster, Robert; Hermann, Manuel M; Rosentreter, Andre; Muether, Philipp S; Kirchhof, Bernd; Fauser, Sascha
Abstract : Background: Aqueous flare as determined by laser flare photometry in the anterior chamber is a strong preoperative predictor for proliferative vitreoretinopathy (PVR) in patients with primary retinal detachment (RD). We analysed various cytokines in aqueous humour samples in relation to aqueous flare and postoperative PVR incidence in patients with RD. Methods: Preoperatively, the aqueous flare of patients with RD was measured quantitatively with a laser flare metre and aqueous humour samples were collected and analysed for interferon γ, tumour necrosis factor α, monocyte chemoattractant protein (MCP)-1, interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-8, vascular endothelial growth factor (VEGF)-A, platelet derived growth factor (PDGF)-aa, transforming growth factor (TGF)-β1, TGF-β2, TGF-β3, fibroblast growth factor (FGF)-aa and FGF-bb by multiplex fluorescent bead-based immunoassays. Three months after RD surgery patients were examined for PVR development. Results: Of 67 consecutive patients, 10 developed at least PVR grade C. Patients with flare values >15 pc/ms (n=20) and the 10 patients with postoperative PVR all had significantly elevated levels of IL-6, IL-8, MCP-1 and TGF-β1 in aqueous humour (p≤0.05). Levels of VEGF-A, PDGF-aa and TGF-β2 were not significantly changed. Other cytokines were below the detection threshold. Eight of the 10 patients (80%) with PVR had elevated flare values of >15 pc/ms and 8 of the 20 patients (40%) with flare >15 pc/ms developed PVR. The OR for PVR with flare values >15 pc/ms was 30.7 (p=0.0001). Conclusions: Laser flare photometry allows simple risk estimation for later PVR development. Elevated laser flare values correspond to an altered profibrotic intraocular cytokine milieu. These factors therefore constitute promising targets for a prophylactic intervention.